French Antarctic Expedition, 1949–52 - Liotard, A.-F.; Barré, M. (Polar Record, 1953)
On 27 February 1947 P.-É. Victor, head of Expéditions Polaires Francaises obtained the agreement of the French Government for the organization of two scientific expeditions, one to Greenland and one to Terre Adélie. Preparations for the French Antarctic Expedition began at once. One of the greatest difficulties which had to be solved was the fact that France had had no polar vessel since the loss of the Pourquoi Pas? in 1936. Eventually, however, Expéditions Polaires FranÇaises bought at San Francisco the Atiette (ex-Lancewood) , a wooden vessel built in 1943 as U.S. Navy net-layer AN-48. This vessel, a sister ship of the John Biscoe and Port of Beaumont, Texas , was brought to France and adapted for polar navigation, the hull being strengthened at the stem and stern. The vessel was then renamed the Commandant Charcot , and the French Navy agreed to commission her and carry the expedition to and from Terre Adélie. Engine trouble delayed the departure originally planned for September 1949, and the vessel did not leave Brest until 26 November that year.